Musculoskeletal manifestations in diabetic versus prediabetic patients. (14th July 2015) - Fatemi, Alimohammad; Iraj, Bijan; Barzanian, Jafar; Maracy, Mohammadreza; Smiley, Abbas
Abstract: Aim: This study was carried out to evaluate the prevalence of musculoskeletal manifestations in a sample of patients with diabetes mellitus (DM) and those with prediabetes and compare the findings between the two groups. Methods: One hundred and eighty‐eight patients with DM and 125 prediabetic subjects were randomly enrolled in this cross‐sectional study. Demographic data and past history were recorded. Musculoskeletal physical examinations were done by a single rheumatologist. Regression analyses were employed to assess the crude and adjusted effects of determinants on DM musculoskeletal manifestations (DMMMs). Results: Female/male ratio was not significantly different between diabetic and prediabetic patients (4.4 vs . 4.7, respectively, P  =   0.9). However, diabetic patients were significantly older than the prediabetic ones (56.6 vs . 52 years, respectively, P  =   0.0001); 83.5% of diabetic patients and 52.8% of prediabetic ones had at least one musculoskeletal manifestation ( P  =   0.0001). The prevalence of knee osteoarthritis and shoulder involvement were almost two times more common ( P  =   0.0001 and P  =   0.015) in diabetic patients than in prediabetic ones (73.4% vs . 38% and 21.2% vs . 9.5%, respectively). Prevalence of carpal tunnel syndrome (CTS) was 48% and 36.5% in patients with diabetes and prediabetes, respectively ( P  =   0.053). Multivariate backward regression analysis showed age, sex, BMI (body mass index) and DM as the significant determinants in development of musculoskeletal manifestations in all subjects. Age and BMI were the only significant factors associated with musculoskeletal manifestations in both diabetic and prediabetic patients. Conclusion: Diabetic and prediabetic patients may show high prevalence of musculoskeletal manifestations. In non‐diabetic patients diagnosed with CTS, prediabetes might be ruled out.